Dissociation between changes in sprinting performance and Nordic hamstring strength in professional male football players - Suarez-Arrones, L.; Lara-Lopez, P.; Rodriguez-Sanchez, P.; Lazaro-Ramirez, J. L.; Di Salvo, V.; Guitart, M.; Fuentes-Nieto, C.; Rodas, G.; Mendez-Villanueva, A. (PLOS ONE, 2018)
The aim of the present study was to evaluate the consequence of implementing a Nordic Hamstring exercise (NHE) protocol during the first 15 to 17 weeks of the season to assess the effect on sprinting and NHE strength (NHEs) in professional football players. The study examined 50 healthy male professional football players (age 18.8±0.8yr; height 176.8±6.9cm; weight 71.3±5.7kg) belonging to 3 of the reserve squads of three Spanish La-Liga clubs divided in 2 intervention teams [Nordic-Group1 (NG-1) and Nordic-Group2 (NG-2, extensive experience in NHE)] and 1 team as a control-group (CG). NHEs and linear sprint (T5, T10, T20-m) were evaluated at the beginning of the season and at the end of an intervention period of conditioning and football training, supplemented with a NHE protocol (24 sessions for NG-1 and 22 sessions for NG-2) or without using the NHE at all (CG). Sprint times were substantially improved in all groups (ES from -2.24±0.75 to -0.60±0.37). NHEs was enhanced absolute and relative to body-mass only in NG-1 after the training period (ES from 0.84±0.32 to 0.74±0.26), while in the NG-2 there were only improvements in average NHEs relative to body-mass (ES = 0.39±0.36). The improvements in T20-m were substantially greater in NG-2 vs. NG-1, and there were no differences in sprint performance changes between NG-1 and CG. Changes in sprinting performance and NHEs were unrelated. NHEs was largely correlated with the body-mass of the players. Results indicate that the improvements in sprint are not dependent on the NHEs changes, with no relationships between NHEs and sprint performance, and between sprint changes and changes in NHEs.